Cranial, nasal, and orbital asymmetry and sexual dimorphism in Turkish adults: a high-resolution 3D morphometric study. - Erdem, Huseyin (Surgical & Radiologic Anatomy, 2025)
Purpose: Despite the increasing use of craniofacial morphometry worldwide, there is a lack of population-specific normative data based on high-resolution 3D skull models for the Turkish population. This study aimed to fill this gap by investigating cephalic, nasal, and orbital indices using precise measurements derived from 3D models, and to evaluate their variations according to sex, age, and laterality. Methods: In this retrospective study, multidetector computed tomography (MDCT) data of 240 adults (120 males, 120 females) without any deformity or trauma were used. Cephalic, nasal and orbital indices were calculated using precise anatomical landmarks on high-precision 3D skull models obtained from these data, and comprehensive statistical analyses were performed with SPSS 20.0. Results: Cranial length, piriform aperture width and orbital width were higher in males than females (p < 0.001). Orbital height was higher in females than in males (p = 0.003). Cephalic and orbital indices were higher in females, whereas nasal index was higher in males (p < 0.001). In terms of anatomical asymmetry, left orbital measurements were higher than the right side in both sexes (p < 0.001). In addition, as age increased, the skull shape shifted towards dolichocephalic type, orbital proportions decreased and nasal aperture widened (p < 0.001). Conclusion: The findings clearly revealed sex-related differences, age-related morphological changes, and significant orbital asymmetry. The obtained data may increase the accuracy of sex estimation in forensic anthropology, support preoperative planning in craniofacial and reconstructive surgeries with region-specific reference measurements, and form the basis for anthropological research by contributing to ethnic and regional morphometric databases.